Methodological dialogues across multimodality and sensory ethnography: digital touch communication. (February 2019) - Jewitt, Carey; Leder Mackley, Kerstin
There is a significant gap between technological advancements of digital touch communication devices and social science methodologies for understanding digital touch communication. In response to that gap this article makes a case for bringing the communicational focus of multimodality into dialogue with the experiential focus of sensory ethnography to explore digital touch communication. To do this, we draw on debates within the literature, and reflect on our experiences in the IN-TOUCH project (2016–2021). While acknowledging the complexities of methodological dialogues across paradigm boundaries, we map and reflect on the methodological synergies and tensions involved in actively working across these two approaches, notably the conceptualization, categorization and representation of touch. We conclude by homing in on aspects of research that have served as useful reflective route markers on our dialogic journey to illustrate how these tensions are productive towards generating a multimodal and multisensorial agenda for qualitative research on touch.